Multiplex array analysis of serum cytokines offers minimal predictive value for cognitive function in the subacute phase after stroke - Zhang, Yuling; Song, Haixin; Wang, Jun; Xi, Xiao; Cefalo, Philip; Wood, Lisa J.; Luo, Xun; Wang, Qing Mei (Frontiers in Neurology, 2022)
Objective The effects of inflammation on post-stroke cognitive function are still unclear. This study investigated the correlation between the Th17-related cytokines in peripheral blood and post-stroke cognitive function after ischemic stroke in the subacute phase. Design A retrospective cohort study. Setting Academic acute inpatient rehabilitation facility. Participants One hundred and fourteen patients with first ischemic stroke were categorized as the poor cognitive recovery group (n = 58) or good cognitive recovery group (n = 56) based on their cognitive MRFS efficiency. Interventions All subjects received routine physical, occupational, and speech-language pathology therapy. Main outcome measures Serum cytokines/chemokine (IL-1 β, IL-2, IL-4, IL-5, IL-6, IL-9, IL-10, IL-12p70, IL-13, IL-15, IL-17A, IL-17E, IL-17F, IL-21, IL-22, IL-23, IL-27, IL-28A, IL-31, IL-33, GM-CSF, IFN-γ, MIP-3 α, TNF-α, and TNF-β) levels were measured in duplicate using Human Th17 magnetic bead panel and multiplex array analysis (Luminex-200 system). The primary functional outcome was a gain in functional independence measure (FIM) cognitive subscore at discharge. The secondary outcome measures were FIM total score at discharge, length of stay in the hospital, and discharge destination. Cognitive Montebello Rehabilitation Factor Score (MRFS) and cognitive MRFS efficiency were calculated. Demographic and clinical characteristics were obtained from the medical record. Results The good cognitive recovery group had an interesting trend of higher IL-13 than the poor cognitive recovery group (good cognitive recovery group 257.82 ± 268.76 vs. poor cognitive recovery group 191.67 ± 201.82, p = 0.049, unit: pg/ml). However, Pearson's correlation analysis showed no significant correlation between cytokine levels and gain of cognition, cognitive MRFS, or cognitive MRFS efficiency. Receiver operating characteristic (ROC) analysis of cytokines also suggested a low accuracy of prediction as a predictor for post-stroke cognitive recovery improvement. Conclusion Our preliminary findings suggested that the level of serum cytokines had minimal predictive value for the recovery of cognitive function during the subacute inpatient rehabilitation after stroke.